IMPLEMENTING COMMUNICATIVE LANGUAGE TEACHING APPROACH AT INNOVATIVE LEARNING CENTER SIDOARJO - dina astriana; Sulistyaningsih (STKIP PGRI SIDOARJO, 2020)
English language is a universal language which is spoken by most countries throughout the world. Teaching English as a Foreign Language (EFL) setting is challenging for teachers. They have to share the English knowledge based on the curriculum and be creative in developing activities in the class. One of the the approaches taught to learners is Communicative Language teaching(CLT) approach.. This study aimed to collect the information on teacher’s comprehension of Communicative Approach and describe the implementation of Communicative Approach conducted by the teachers. The subject of this study was five English teachers at Innovative Learning Center, Sidoarjo. The observer collected the data from questionnaires, interview and observation.The findings showed that 4 teachers (80%) understood about the communicative language teaching approach and all of them (100%) have conducted the communicative approach in the English teaching process.